Folate and Vitamin B‐12 Status Is Associated With Bone Mineral Density and Hip Strength of Postmenopausal Chinese‐Singaporean Women. (2nd September 2020) - Kalimeri, Maria; Leek, Francesca; Wang, Nan Xin; Koh, Huann Rong; Roy, Nicole C; Cameron‐Smith, David; Kruger, Marlena C; Henry, Christiani Jeyakumar; Totman, John J
ABSTRACT: The role of micronutrients such as folate and vitamin B‐12 in bone quality has been widely studied with conflicting results. Ethnicity seems to play a large role on nutrient intake, as diet varies across cultures. In this study, we examined the relationships of BMD, proximal femur strength, and bone resorption with plasma folate and vitamin B‐12 in a cohort of 93 healthy postmenopausal women of Chinese‐Singaporean descent. The parameters examined were areal (aBMD) and volumetric BMD (vBMD) of the proximal femur and the third lumbar vertebra (L3), total body aBMD, proximal femur bending, compressive and impact strength indices (composite strength indices) and circulating levels of C‐telopeptide of type I collagen. Eighteen participants (19.4%) had aBMD in the osteoporotic range (osteoporosis group), 59 (63.4%) in the osteopenic range (osteopenia group), and the remaining 16 (17.2%) in the normal range (normal BMD group). Circulating folate levels were significantly higher in the normal BMD group compared with the osteoporosis group. Using linear regression analysis, we found that overall, aBMD and vBMD are positively associated with folate concentrations, whereas composite strength indices were positively associated with vitamin B‐12 concentrations. These findings support the existing literature and suggest a link between levels of circulating folate/vitamin B‐12 and BMD/bone strength in the cohort examined. Further investigation is needed to examine if individuals with inadequate circulating levels of these nutrients could decrease their risk for fragility fractures through better nutrition or vitamin supplementation. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.